Science Kingdom as a Tool to Support High School Chemistry Teaching - Monteiro da Silva, Nathan de Andrade; Sousa, Pedro Moises de (Anais do Workshop de Sistemas de Informação (WSIS); 2024: Anais do XV Workshop de Sistemas de InformaçãoDO - 10.5753/wsis.2024.33688, 2024)
This article describes the development, planning and evaluation of a digital educational game aimed at teaching chemistry in schools, with a focus on high school students. The game uses the Unity 3D game engine and aims to facilitate the learning of concepts such as the periodic table, atomicity and chemical reactions, offering a more dynamic approach to teaching. Implementing the agile methodology, a usability test was carried out in one school with teenagers aged between 14 and 17. This article examines the creation of Science Kingdom, the digital role-playing game, its instigations and pre-results, contributing to the debate on the use of digital games in teaching.